Peran Kantor Desa Blahbatuh dalam Meningkatkan Partisipasi Masyarakat Terhadap Administrasi Kependudukan - Ida Ayu Gede Adi Suandewi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
To address various problems related to population, the government seeks to obtain accurate population data in Indonesia to be able to make an appropriate mapping to deal with population problems. This study aimed to reveal the role of the Blahbatuh Village Office in increasing community participation in population administration and to explain the factors that influence the low participation of citizens to report population events in Blahbatuh Village. The research method used was empirical law with a field research approach. The main data was obtained through interviews and observations. The analytical model used was qualitative data. The results showed that the role of the Blahbatuh Village Office in increasing community participation in population administration was to provide counseling, to socialize with the community about the importance of Population Administration. Furthermore, prioritizing service to the community based on conscience. The low community participation in population administration reporting is the low community participation in implementing village regulations, and the work system that has not been implemented properly